2013
DOI: 10.2478/physio-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle exercise as the best stress urinary incontinence prevention method in women practising competitive sport

Abstract: Exercises in stress urinary incontinence (SUI) cover Pelvic Floor Muscle Exercises (PFME), also known in literature as Pelvic Floor Muscle Training (PFMT) or Kegel exercises; isometric exercises, exercises of the abdominal and gluteal muscles and of the adductor of thigh, respiratory exercises carried out through the abdominal tract, exercises in water. In persons with urinary incontinence, the interaction between the pelvic floor muscles and the transverse abdominal muscle is impaired, suggesting a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Neumann et al 1 demonstrated that specialized ambulatory physiotherapy was a low-cost, low-risk and effective treatment, which should be offered as a first-line treatment for stress urinary incontinence. Similar positive findings were also reported by Balmforth et al 28 and Opara et al 29 highlighting the potential role for physiotherapy-led initiative for women with urinary incontinence and/or POP symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…Neumann et al 1 demonstrated that specialized ambulatory physiotherapy was a low-cost, low-risk and effective treatment, which should be offered as a first-line treatment for stress urinary incontinence. Similar positive findings were also reported by Balmforth et al 28 and Opara et al 29 highlighting the potential role for physiotherapy-led initiative for women with urinary incontinence and/or POP symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…They are as follows: (1) Stress UI (SUI), which occurs most often and accounts for about 50-70% of all types of UI, occurs when leakage of urine is caused by a sudden increase in pressure inside the abdominal cavity due to sneezing, laughing, jumping, bending, squatting, sudden change of body position, or when lifting heavy objects without the feeling of pushing on the bladder. SUI occurs as a result of weakened pelvic floor muscles and accompanying ligaments; 2,[13][14][15][16] (2) Urge incontinence, which is associated with the autonomic nervous system and consists of involuntary urination accompanied by a feeling of pushing. The amount of urination is high and the main causes are central nervous system (CNS), spinal cord, Parkinson's disease and dementia damage.…”
Section: Urinary Incontinence In Womenmentioning
confidence: 99%
“…That is why it is so important to mobilize women to change their lifestyle to a healthier one; to reduce body weight (especially the percentage of body fat ratio), to limit the use of stimulants, to prevent constipation and to use systematic physical activity. 11,14,73 Conclusion BF has become an increasingly popular method of UI treatment, at the same as time teaching women self-awareness of their bodies and the physiological processes taking place in them. Insufficient information on treatment options, prevention methods and possible complications resulting from not treating this embarrassing disease is worrying.…”
Section: Prevention Of Urinary Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…There are many risk factors for urinary incontinence, including: being female, menopausal age, obesity, previous births, hysterectomy and other gynecological operations, smoking, constipation, genetic factors, estrogen deficiency, heavy physical work or intensive training [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%